Effect of cooking classes for housewives on salt reduction in family members: a cluster randomized controlled trial. (November 2016) - Takada, T.; Imamoto, M.; Fukuma, S.; Yamamoto, Y.; Sasaki, S.; Uchida, M.; Miura, Y.; Shimizu, S.; Nihata, K.; Fukuhara, S.
Abstract: Objectives: Sodium reduction is very important in preventing cardiovascular diseases, especially in regions with high salt intake such as Japan. One strategy for salt reduction is to raise consumer awareness of the need to reduce daily salt intake. We investigated whether cooking classes given to housewives focussing on salt reduction would influence not only their own consumption behaviour but also that of their family members. Study design: Single-blinded, cluster randomized trial. Methods: We randomly assigned housewives to participate in cooking classes focussing on salt reduction (intervention group) or lectures about a healthy lifestyle (control group). The main outcome measure was the difference in estimated daily salt intake by spot urine sampling of housewives and their family members 2 months after intervention between the groups. Results: A total of 35 housewives and 33 family members were randomized. The mean daily salt intake was 10.00 (standard deviation [SD] 1.75) g/day in the control group (17 housewives and 15 family members) and 9.57 (SD 2.45) g/day in the intervention group (18 housewives and 18 family members) at baseline. Two months after the intervention, the mean salt intake was 10.30 (SD 1.78) g/day in the control group and 8.95 (SD 2.45) g/day in the intervention group. The mean difference was −1.19 g/day (95% confidence interval −2.29, −0.09; P  = 0.034). A similar tendency was observed in the subgroups of housewives and family members. Conclusions: Our trial suggested that the effects of cooking classes focussing on salt reduction for housewives could be transferred to family members (UMIN-CTR: 000018870). Highlights: We assessed the effect of salt reduction in housewives conveyed to their family. The mean difference in salt intake for housewives and family members was −1.19 g/day. The subgroups of housewives and family members showed similar tendency. The effects of cooking classes for housewives could be transferred to family members.